Assessment of the hydrological drought risk in Calgary, Canada using weekly river flows of the past millennium. Issue 4 (1st March 2022) - Gurrapu, Sunil; Sauchyn, David J.; Hodder, Kyle R.
Abstract: Planning and management of water resource infrastructure requires a depth of knowledge on the characteristics of hydrological extremes, floods and droughts. Infrastructure design is traditionally based upon historically observed extreme events, assuming that they are independent and identically distributed ( i.i.d. ) and stationary, i.e. they fluctuate within a fixed envelope of variability. Information on historical hydroclimate provides a limited range of hydrological extremes, which rarely includes long-term worst droughts. This study demonstrates the application of a paleo-environmental dataset, 900 years of weekly streamflow stochastically derived from a tree-ring reconstruction of annual streamflow, to assess the hydrological drought risk. The historic and prehistoric hydrological drought characteristics, i.e. severity–duration–frequency (SDF) relationships, are evaluated. The results indicate that the severity and duration of hydrological drought with the same recurrence interval is substantially larger and longer than those observed over the 100-year historical period. Historic and prehistoric drought SDF relationships established in this study demonstrate the implications of non-stationary climate in the analysis of extreme droughts. Therefore, projected droughts of the 21st century may not exceed the drought severity found in the prehistoric record to the same extent that they exceed historical droughts in the instrumental record. This study emphasizes the importance of paleohydrology in comprehending the region's drought. HIGHLIGHTS: The results from the study indicate that the drought characteristics over the past millennium differed substantially from those which occurred over the past century. Defining drought response triggers based on the historical data alone could underestimate the potential drought severity. Our results also indicate that it is irrational to assume stationary climate in determining the frequency of severe droughts.